Structural Integration of Carbazole and Tetraphenylethylene: Ultrafast Excited‐State Relaxation Dynamics and Efficient Electroluminescence. Issue 4 (25th February 2021) - McGregor, Sarah K. M.; Govind, Chinju; Wood, Michael K. R.; Shukla, Atul; Lim, Hyunsoo; Lepage, Romain J.; Krenske, Elizabeth H.; K. N., Narayanan Unni; Ajayaghosh, Ayyappanpillai; Karunakaran, Venugopal; Namdas, Ebinazar B.; Lo, Shih-Chun
Abstract : The synthesis, characterization, and spectroscopic investigations of a new solution‐processable N ‐styrylcarbazole‐linked tetraphenylethylene (TPE) derivative (TPE‐BCzS ) are reported, exhibiting green–orange emission. While the material displays weak photoluminescence (PL) in solution with a low PL quantum yield (PLQY of 4 ± 0.2%), significant PL enhancement in neat‐film PLQY (55 ± 8%) is observed. Studies using steady‐state spectroscopy, and femtosecond and nanosecond transient absorption spectroscopy reveal details of the excited‐state dynamics, consisting of the Franck–Condon (FC) state, nonradiative conformational relaxation, and formation and decay of the triplet excited state generated via intersystem crossing (ISC) upon ultrafast photoexcitation. Solution‐processed organic light‐emitting diodes (OLEDs) based on TPE‐BCzS display maximum external quantum efficiencies of 1.8% and 1.7% for neat and blend films (20 wt% in a 4, 4′‐bis( N ‐carbazolyl)‐1, 1′‐biphenyl host), approaching the theoretical efficiency limit for the determined PLQYs of the films. While TPE materials are typically associated with aggregation‐induced emission, it is reported that the enhanced PLQYs in the solid state are due to restriction of structural relaxations in the solid state and not due to the commonly misunderstood aggregation effect. Abstract : An in‐depth investigation using steady‐state spectroscopy, and femtosecond and nanosecond transient absorption spectroscopy facilitates a deeper understanding of the structural origin of the emissive species from a novel tetraphenylethylene (TPE) material, TPE‐BCzS . The enhanced emission in solid state due to restriction of structural relaxations—not intermolecular aggregation—is established.